Sosialisasi Konservasi Penyu Laut Berbasis Edukasi di SMPN 1 Desa Keude Panga Kecamatan Panga Kabupaten Aceh Jaya Provinsi Aceh - Mohamad Gazali; Supriadi Supriadi; Masyumi masyumi; Irham Dika (Universitas Teuku Umar, 2017)
According to observation and interview that undertaken in Panga District Aceh Jaya Regency that there are 3 species of sea turtle with coastal line is 9.3. km. The third of such sea turtle including Olive ridley sea turtle(Lepidochelys olivacea), hawkbill sea turtle (Eremochelys imbricate), leatherback sea turtle (Dermochelys coriacea). The target of community that involved in socialization of sea turtle are student of junior high school. Earlier education to young generation regarding the important of sea turtle conservation educated-based is the effort for keeping sea turtle in natural with undertook the socialization to young generation in order to grow a caring and loving to sea turtle sustainablity. Coastal community still undertook to hunting sea turtle’s eggs for trading in the traditional market dan restaurants. It is caused by lack of understanding and awareness regarding sea turtle that threaten scarce. In this activity, the researcher will undertake persuasive approaach and solutive in changing a mindset of young generation gradually that inhabit in near nesting site. In this activity including suvey activity prior to socialization that near the nesting site, socialization activity in the SMPN 1 Panga that selected as target school in the socialization of Sea Turtle Conservation, conducting the retelling story games, and conducting hatchlings release programme to the sea with community elements.